5x-2x-9=x-3

Simple and best practice solution for 5x-2x-9=x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-2x-9=x-3 equation:


Simplifying
5x + -2x + -9 = x + -3

Reorder the terms:
-9 + 5x + -2x = x + -3

Combine like terms: 5x + -2x = 3x
-9 + 3x = x + -3

Reorder the terms:
-9 + 3x = -3 + x

Solving
-9 + 3x = -3 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-9 + 3x + -1x = -3 + x + -1x

Combine like terms: 3x + -1x = 2x
-9 + 2x = -3 + x + -1x

Combine like terms: x + -1x = 0
-9 + 2x = -3 + 0
-9 + 2x = -3

Add '9' to each side of the equation.
-9 + 9 + 2x = -3 + 9

Combine like terms: -9 + 9 = 0
0 + 2x = -3 + 9
2x = -3 + 9

Combine like terms: -3 + 9 = 6
2x = 6

Divide each side by '2'.
x = 3

Simplifying
x = 3

See similar equations:

| -18=6+12k | | Y+2=40 | | 4e^5x=644 | | 3-(2x-8)= | | 5x-2x-9=3x-17 | | 36-a=36 | | 3x+25=28 | | 7e^8x=1015 | | 3e^7x=756 | | d(x)=0.04x^2+2x | | 7y-34+9x-4=180 | | 0.6(2.4a-1.4)=6 | | 6(x-1)-4=14 | | 3y+7=3y-12 | | 12-.5x=7 | | (34+13i)-(-2-17i)+(16+25i)=0 | | x+10y=-8 | | 7+m=20 | | p^2=6p+16 | | 8(t+8)=96 | | 9y+28=120 | | 3(5x+2)=8x-5 | | -1+2x=-7 | | 3x+7y-21=10xy+(-21) | | 5.75x-10=9.25+2 | | -6.1n-3.9n= | | 13y=4y+36 | | 13.50/20= | | 10y+4=124 | | 36=3(x+6) | | 9x^2-6x+k=0 | | i(3+2i)(3+2i)=0 |

Equations solver categories